Main problems of mine drum design - Fidrovska, Nataliia Mykolaivna; Slepuzhnikov, Yevhen Dmytrovych; Nesterenko, Viktoriia Valentynivna; Musaiev, Zaur Razylovych; Фідровська, Наталія Миколаївна; Слєпужніков, Євген Дмитрович; Нестеренко, Вікторія Валентинівна; Мусаев, Заур Разилович (Харківський національний автомобільно-дорожній університет, 2023)
The article deals with the problems of mine drums, namely, an adjusted approach to the justification of their design, and suggests ways to improve their performance. The practice of designing mine drums is based on the introduction of additional stiffening elements, such as ribs, rings and scarves. This significantly increases the weight and complexity of the drum manufacture, and also leads to local stresses in the welded areas. This greatly complicates the operation of the structure and leads to the destruction of welds and the appearance of cracks. Reinforcing the welds does not improve the situation, but rather reduces the durability of the drum shell. Designers of mine hoisting machines do not have a theoretical basis for refusing to install rings and stiffeners. The calculations of the strength of the drum head using the simplified and refined methods showed that the strength of the head is fully ensured and there is no need to install additional structures in the form of scarves.
Основні проблеми конструкції шахтних барабанів
Keywords: mine drum; frontal liner; shell; strength; bending moment; stress; scarf; stiffening elements; шахтний барабан; лобовина; обичайка; міцність; момент згину; 621.863; 10.30977/BUL.2219-5548.2023.101.2.142